Analysis of condition microcirculatory level of the maxillofacial area by using laser doppler flowmetry - Maksymov, D. Y.; Максимов, Денис Янович (НУОЗ ім.П. Л. Шупика, 2022)
The aim of the study: is to identify the possibility of using Doppler laser flowmetry in dentistry.
Аналіз стану мікроциркуляторного русла щелепно-лицевої ділянки шляхом використання лазерної доплепровської флоуметрії
ORCID: 0000-0002-3200-3754